2014
DOI: 10.1063/1.4891194
|View full text |Cite
|
Sign up to set email alerts
|

Highly transparent and flexible InTiO/Ag nanowire/InTiO films for flexible organic solar cells

Abstract: We investigated characteristics of Ti-doped In2O3 (TIO)/Ag nanowire (NW)/TIO films as potential transparent and flexible electrodes for flexible organic solar cells. Effective insertion of metallic Ag NW between TIO layers led to improvement of electrical and mechanical properties of sputtered TIO film. At optimized conditions, we achieved a flexible TIO/Ag NW/TIO multilayer with a low sheet resistance of 9.01 Ω/square and a high optical transmittance of 85.14%. In addition, the TIO/Ag NW/TIO multilayer electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…3b ). The main conduction path in this OCO multilayer electrode is likely to be the metallic Cu interlayer, similar to previously reported OMO multilayer electrodes 20 21 22 . To elucidate the electrical contribution of the Cu layer in the as-deposited OCO multilayer, the sheet resistance and resistivity of inserted thin Cu layer were extracted using the following equation (1 ) and ( 2 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…3b ). The main conduction path in this OCO multilayer electrode is likely to be the metallic Cu interlayer, similar to previously reported OMO multilayer electrodes 20 21 22 . To elucidate the electrical contribution of the Cu layer in the as-deposited OCO multilayer, the sheet resistance and resistivity of inserted thin Cu layer were extracted using the following equation (1 ) and ( 2 ).…”
Section: Resultssupporting
confidence: 90%
“…Although Kim et al reported the low sheet resistance (6.197 Ohm/square) and high transmittance (90.65%) of Cu honeycomb mesh covered by Al-doped ZnO film, the high reflectivity of Cu metal grid is still problem to use as transparent electrodes for TSPs 19 . Recently, oxide-metal-oxide (OMO) multilayer electrodes have emerged as promising transparent electrodes for flexible organic light emitting diodes, flexible organic solar cells, flexible TSPs, flexible memory devices, and flexible oxide thin films transistors due to its low resistivity, high transmittance and good flexibility due to their low resistivity, high transparency and mechanical flexibility 20 21 22 23 24 25 26 27 . However, OMO multilayer films such as, ITO/Ag/ITO, IZO/Ag/IZO, and IZTO/Ag/IZTO still contain the high-cost elements of indium and silver.…”
mentioning
confidence: 99%
“…However, typical Ag NW network still showed critical problems such as poor adhesion, irregular morphology, and time-dependent degradation. To solve those problems, Ag NW-based hybrid electrodes such as ITO/Ag NW/ITO, ZnO/Ag NW/ZnO, and Ti-doped In 2 O 3 (TIO)/Ag NW/ TIO have been suggested [11][12][13][14][15]. Effective insertion of Ag NW into oxide films led to low resistivity and high flexibility of the hybrid electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, direct current (DC)-sputtered ITO films and printed PEDOT:PSS films have been the materials most commonly used as transparent anodes for conventional bulk heterojunction OSCs, although mismatched band alignment of ITO anodes and instability of PEDOT: PSS films still remain as critical problems [12,13]. To substitute ITO and diversify the anode materials available for OSCs, various transparent conducting oxide (TCO) films have been prepared by [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. By the way, several sputtering techniques such as facing target sputtering, cylindrical sputtering, roll-to-roll sputtering, and combinatorial sputtering have been reported as technique for coating TCOs used in OSCs.…”
Section: Introductionmentioning
confidence: 99%